2015
DOI: 10.1080/07373937.2015.1087408
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model for intermittent microwave convective drying of food materials

Abstract: Intermittent microwave convective drying (IMCD) is an advanced technology that improves both energy efficiency and food quality in drying. Modelling of IMCD is essential to understand the physics of this advanced drying process and to optimize the microwave power level and intermittency during drying. However, there is still a lack of modelling studies dedicated to IMCD. In this study, a mathematical model for IMCD was developed and validated with experimental data. The model showed that the interior temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(52 citation statements)
references
References 45 publications
2
44
0
6
Order By: Relevance
“…41 The spectrum of CNC showed characteristic absorption bands at around 2900 cm À1 , 3000 cm À1 and 1430 cm À1 , which belong to C-H stretching, O-H stretching and CH 2 scissoring band, respectively. 42 A higher absorption from 3600 cm À1 to 3200 cm À1 appeared in the spectrum of SA/Ge/CNC scaffold, which suggested an increase of hydrogen bonds resulting from the interaction between SA/Ge backbone and CNC. 36 The results of FTIR indicated the presence of CNC in the hybrid scaffold as wells as the interaction between them.…”
Section: Morphology and Chemical Evaluation Of Cnc And Sa/ge/ Cnc Scamentioning
confidence: 94%
“…41 The spectrum of CNC showed characteristic absorption bands at around 2900 cm À1 , 3000 cm À1 and 1430 cm À1 , which belong to C-H stretching, O-H stretching and CH 2 scissoring band, respectively. 42 A higher absorption from 3600 cm À1 to 3200 cm À1 appeared in the spectrum of SA/Ge/CNC scaffold, which suggested an increase of hydrogen bonds resulting from the interaction between SA/Ge backbone and CNC. 36 The results of FTIR indicated the presence of CNC in the hybrid scaffold as wells as the interaction between them.…”
Section: Morphology and Chemical Evaluation Of Cnc And Sa/ge/ Cnc Scamentioning
confidence: 94%
“…It is based on the assumption that any continuous quantity such as moisture content can be approximated by a discrete model composed of a set of piecewise continuous functions defined over a finite number of sub‐domains or elements (Segerlind, ). In recent past few researchers have developed the FE based heat and mass transfer model during drying of food products such as for prunes (Sabarez, ), banana (Kumar et al, ), yam (Ju et al, ), and apple (Rahman, Kumar, Joardder, & Karim, ). However, Janjai et al () developed a two‐dimensional FE model based purely on mass transfer, neglecting heat transfer and its effect on drying, to simulate moisture diffusion in mango.…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully used to extract pectin since it avoids overheating and is better at balancing heat of samples during mass transfer processes [3]. The improved efficiency of intermittent microwave extraction compared to the continuous process is also because of efficiency of the pulsed heat supply [4]. Swamy and Muthukumarappan [5] showed that intermittent processing yielded higher pectin retrieval from banana peel compared to continuous processing microwave extraction (MAE), and is also comparable to other modern extraction techniques including supercritical fluid extraction (SFE), subcritical water extraction (SWE) and ultrasoundassisted extraction (UAE), due to its simplicity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully used for the extraction of pectin from the peel of fruit. Pectin consists of a backbone of α-D- (1,4) galacturonic acid (GalA) residues, which are partially esterified with methyl alcohol or acetic acid in carboxylic acid. Pectin is classified into high methoxyl and low methoxyl pectin, depending on whether its degree of esterification (DE) is greater or less than 50% [7].…”
Section: Introductionmentioning
confidence: 99%